Die sheet hydroforming of a complex shaped AA2024-W Aircraft skin panel – from concept to final component - Serfontein, Jean-Pierre Louis (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.